Corona, command and capitalism. Issue 3 (25th July 2020) - Ward, Michael
Abstract : Learning outcomes: The case presents a lot of information, directly and via references and Web-based links, about the economic consequences of the virus. Several themes are evident: As an opening theory-base, the decades-long stakeholder versus shareholder debate is invoked – but does this extend beyond "stakeholders" to the "public good"? There are contexts (generally wars) in which governments are empowered to instruct private companies to engage in the public good – but how far should/must they voluntarily go? The underlying macro-economic issue is: where will we get the capital? Central banks have not recovered from the 2008 global financial crisis and have limited "ammunition" to address the anticipated economic problems introduced by the virus. The case presents data on selected financial metrics (interest rates, debt levels, risk pricing, etc.) and outlines the conventional stimulatory steps used: lowering short-term rates (monetary policy) and investment in assets (fiscal policy) and the less-conventional Quantitative Easing "QE". Case overview/synopsis: The coronavirus appears to herald a devastating blow to lives and to the world economy – its impact is yet unknown, but likely to be comparable to war and pestilence of biblical proportion. This case focuses on the possible economic trajectories as a consequence of the virus, with emphasis on bailing-out (restructuring) struggling companies and restoring jobs. Within the framework of a world desperately in need of capital, it raises questions about accountability and responsibility. Should retrenched workers in restaurants, banks and airlines feel the consequences of their poor career choices? Must shareholders (read pensioners) shoulder losses to support the public good? Ought governments bail-out whole industries – using tax-payer money? Or do we allow central banks to conjure-up billions and hope for the best? The case does not attempt to provide answers to these questions but presents several vignettes and offers a context in which participants can debate the merits of these problems. Complexity academic level: MBA and Exec-ed. Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS: 1 Accounting and Finance.